Autonomous Underwater Robot for Water Quality Measurement of Northwest Pennsylvania Lakes - Pallas-Athena Cain; Trang Hoang; Janyl Jumadinova (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
The Northwestern Pennsylvania Region, notably affected by toxic algae blooms like those in Lake Erie, suffers from a lack of adequate water quality monitoring tools. This project aims to bridge this gap through the development of cost-effective underwater robots designed to gather critical water quality data. The software developed for this project facilitates the generation of analytics essential for assessing the health of aquatic environments. The robots engineered through this project are set to be deployed by the local Conservation District for routine water quality monitoring activities.